2016
DOI: 10.1177/0954406215607902
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of partially connected parallel beams with elastically restrained ends

Abstract: In the present paper, the problem of transverse free vibration of two parallel beams partially connected to each other by a Winkler-type elastic layer is investigated. Euler–Bernoulli beam hypothesis has been applied, and translational and rotational elastic springs in each end considered as support. The motion of the system is described by coupled, piece-wise differential equations. The differential transform method (DTM) is employed to derive natural frequencies and mode shapes. DTM is a semi-analytical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…According to the results of Ref. [19], a partial removal of the elastic layer was considered as damage at the core did not a ect the odd mode frequencies of the system; consequently, through the usual methods of modal parameters, detecting the core damage is not easily possible and, so far, no research has been done in this area, while damage at the core is detected by the current method, even in the presence of excessive noise; 5. The accuracy of the method in the presence of noise depends on the location of the damage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of Ref. [19], a partial removal of the elastic layer was considered as damage at the core did not a ect the odd mode frequencies of the system; consequently, through the usual methods of modal parameters, detecting the core damage is not easily possible and, so far, no research has been done in this area, while damage at the core is detected by the current method, even in the presence of excessive noise; 5. The accuracy of the method in the presence of noise depends on the location of the damage.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, their study deals with the e ect of damage in the inner elastic layer on natural frequencies and mode shapes. Results in [19] showed that for similar boundary conditions of upper and lower beams, damage to the core did not a ect odd mode frequencies. Nguyen [20] addressed the e ect of crack on the double-beam system by applying Finite Elements (FE) method.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, their study deals with effect of damage in the inner elastic layer on natural frequencies and mode shapes. Results of [29] show that for similar boundary conditions of upper and lower beams, damage in core does not affect odd mode frequencies. Nguyen [30] addressed effect of crack on double beam system by using finite elements method and used results to crack detection.…”
Section: Introductionmentioning
confidence: 87%
“…In these researches, the beams and core are intact and effects of damage are neglected. Mirzabeigy and Madoliat [29] investigate the free vibration of the partially connected double-beam system. In fact, their study deals with effect of damage in the inner elastic layer on natural frequencies and mode shapes.…”
Section: Introductionmentioning
confidence: 99%